(untitled) (Encuentros, 2016)
This article presents the results of the analysis that has been done in Ibagué, a colombian city, about the dynamics of street art in the urban public space. The research studied the processes of formation of graffiti crews, the relationship between graffiti, government and the citizen’s perception about this practice. Theses dynamics begun to be studied in june 2013 in a broader research that included two stages: the first aimed at the revision of the regulations on public space and street art and the analysis of news published in the local newspaper, El Nuevo Día. The second stage was the application of questionnaires and interviews with graffiti artists. Key words: Graffiti, cultural practices, urban art, public space, urban space, youth, identity